Humdrum Tasks of the Salaried Men: Edwin Williams, a London County Council Architect at War - Nick Beech (Footprint)
Working at the London County Council Architects’ Department through the 1930s to 1950s, and known (if at all) as a member of the design team for the Royal Festival Hall, Edwin Williams is usually presented as a regressive figure, his design work marked by his Beaux Arts training. Using archival evidence and histories of the construction industry, this paper sets out Williams’s role in the organisation of rescue and recovery services in London during the Second World War. The paper argues that through his development of training schools and curricula for Rescue Service personnel, Williams played a key role in the formation of a skilled, mechanised, modern demolition industry. Operating complex emergency projects under extreme conditions, the same contractors and building operatives trained in Williams’s programme were later responsible for the clearance of bomb damaged sites and slums. This paper suggests that certain developments in modern architecture can be considered contingent upon practices of the demolition industry as developed by Williams. By concentrating on the ‘organisation’ and ‘progress’ of production that architects engaged with during the Second World War and after, new configurations of continuity and change emerge in which the ‘humdrum tasks’ of ‘salaried men’ appear crucial.